Brown and red shades in the riverbed of the Nera River (Serbia) – update on the distribution and ecology of the association Hildenbrandio rivularis–Heribaudielletum fluviatilis Fritsch 1929 corr. Täuscher 2020 in Southeastern Europe - Trbojević Ivana; Milovanović Vanja; Sekulić Jasmina Šinžar; Sekulić Nenad; Krizmanić Jelena; Simić Gordana Subakov (Oceanological and Hydrobiological Studies)
Heribaudiella fluviatilis (Areschoug) Svedelius is one of the rare representatives of freshwater brown algae, and its range is restricted to the Northern Hemisphere. Hildenbrandia rivularis (Liebmann) J. Agardh is still one of the endangered red algae species in Europe, although its indicator value and distribution have recently been questioned. The association Hildenbrandio rivularis– Heribaudielletum fluviatilis Fritsch 1929 corr. Täuscher 2020 occurs mainly in Northern and Central Europe, while its occurrence and ecology in Southern Europe are poorly researched. The lower reaches of the Nera River near the small town of Bela Crkva, Serbia, were searched for macroalgae in August 2021 and June 2022, when stones with macroalgal crusts were collected. Environmental parameters were measured in situ and water samples were collected for further analysis. A sample of the epilithic diatom community was collected to calculate diatom indices. We present the occurrence of the association Hildenbrandio rivularis–Heribaudielletum fluviatilis in the lower course of the Nera River in Serbia, relating the ecology of the species and habitat to previous findings from the Southeast European region. We discuss potential indicator values of macroalgae associations, rather than of a single species.